2014
DOI: 10.1002/dvdy.24234
|View full text |Cite
|
Sign up to set email alerts
|

Wnt and FGF mediated epithelial‐mesenchymal crosstalk during lung development

Abstract: The adaptation to terrestrial life required the development of an organ capable of efficient air-blood gas exchange. To meet the metabolic load of cellular respiration, the mammalian respiratory system has evolved from a relatively simple structure, similar to the two-tube amphibian lung, to a highly complex tree-like system of branched epithelial airways connected to a vast network of gas exchanging units called alveoli. The development of such an elaborate organ in a relatively short time window is therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 271 publications
3
118
1
Order By: Relevance
“…This is the first study to demonstrate a deficiency in MSC expression of FGF-10 in progressive IPF, a specific clinical endotype. This is consistent with a protective role of FGF-10 in animal models of lung injury and fibrosis24404359. Further studies are required to determine the impact of the FGF-10 deficiency on epithelial cell fate and function.…”
Section: Discussionsupporting
confidence: 76%
“…This is the first study to demonstrate a deficiency in MSC expression of FGF-10 in progressive IPF, a specific clinical endotype. This is consistent with a protective role of FGF-10 in animal models of lung injury and fibrosis24404359. Further studies are required to determine the impact of the FGF-10 deficiency on epithelial cell fate and function.…”
Section: Discussionsupporting
confidence: 76%
“…The Wnt signaling pathway is critical for lung endoderm specification and patterning of the branching lung and mesenchyme (Cohen et al, 2009; Goss et al, 2009; Harris-Johnson et al, 2009; Kadzik et al, 2014; Li et al, 2002; Miller et al, 2012; Mucenski et al, 2003; Rajagopal et al, 2008; Volckaert and De Langhe, 2015). However, the role for Wnt signaling during lung sacculation and alveologenesis is poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…Since many components of the Hippo pathway (Fig. In addition, since the Hippo pathway has been shown to interact with many other pathways such as the Wnt pathway, which is critical for lung homeostasis, 93 it will be very interesting to further explore how the Hippo interacts with these known Hippo-interacting signaling pathways or identify novel signaling pathways interacting with the Hippo signaling in regulating lung development, tumorigenesis and metastasis. In addition, we and others have shown that the Hippo pathway is involved in many aspects of cancer progression and therapy such as drug resistance.…”
Section: Discussionmentioning
confidence: 99%